CARTOGRAPHICAL ALGORITHM OF EFFICIENT CULLING OF VECTORIAL OBJECTS (Journal of Information Technologies in Education (ITE), 2010)
Algorithm, presented in the article, demonstrates an effective model of processing of vectorial objects in GIS, in particular visualization
Keywords: algorithm; efficiency; GIS; vectorial; visualization